Aligned gold nanobowl arrays: their fabrication, anisotropic optical response and optical grating applications. Issue 1 (24th November 2014) - Li, Xinyang; Wu, Yanchun; Hang, Lifeng; Men, Dandan; Cai, Weiping; Li, Yue
Abstract : Aligned Au nanobowl arrays on a flexible film with specific optical properties were obtained by combining template-assisted self-assembly and colloidal lithography. Abstract : A simple, low-cost and high-throughput technique to fabricate aligned Au nanobowl arrays is presented by combining template-assisted self-assembly and colloidal lithography. Polystyrene (PS) colloids were self-assembled into the aligned grooves on a blank digital versatile disc (DVD) substrate, forming aligned PS colloidal necklace arrays. After being coated with an Au layer, they were inverted onto another glass slide with a polyvinyl alcohol (PVA) thin layer and aligned Au nanobowl arrays were obtained after peeling off the DVD substrate and removing the PS colloidal spheres. If the glass slide substrate was removed, the aligned Au nanobowl arrays on a flexible PVA substrate could be achieved. These Au nanobowl alignments displayed higher reflectance and could be used as an optical grating. They also demonstrated anisotropic optical properties and have important potential applications in optical devices, such as optical gratings, waveguide, and so on. This work will provide new insights and understanding of the control of morphology and enhancement of optical properties of Au nanoparticle arrays and it is helpful to develop new optical devices based on such anisotropic optical performance.